Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
Dale Blickenstaff, Justice Charles Hamlin, and Judge Frank Creede, Jr. 5080 E. Kings Canyon Road, Fresno